Association of the CYP2B6 gene with anti-tuberculosis drug-induced hepatotoxicity in a Brazilian Amazon population - Débora Christina Ricardo Oliveira Fernandes; Ney Pereira Carneiro Santos; Milene Raiol Moraes; Ana Cristina Oliveira Braga; Cleonardo Augusto Silva; Andrea Ribeiro-dos-Santos; Sidney Santos (International Journal of Infectious Diseases, 2015)
Objectives: The treatment of tuberculosis (TB) remains a challenge owing to the high incidence of drug-induced hepatotoxicity. The aim of this study was to examine the effect of two gene polymorphisms, one in the CYP2B6 (rs3745274) gene and one in the CYP3A5 (rs776746) gene, on the development of hepatotoxicity in patients treated with anti-TB drugs in a Brazilian Amazon population. Methods: TB patients who were treated with anti-TB drugs were examined for hepatotoxicity, an adverse effect that is characterized by liver damage. The genotype frequencies of the CYP2B6 and CYP3A5 genes examined in this study were assessed using RT-PCR. Results: Thirty-one of the 220 subjects (14.1%) included in this study developed drug-induced hepatotoxicity. The result was significant when the TT homozygous mutant of the CYP2B6 gene was analyzed with additional key variables (p = 0.046; odds ratio (OR) 0.063, 95% confidence interval (CI) 0.004–0.955), which may explain the hepatotoxicity results in this study. Using a univariate statistical model to associate the CYP3A5 gene A6986G polymorphism with the examined drugs, the results did not differ between samples from individuals with and without hepatotoxicity (p = 0.176; OR 0.562, 95% CI 0.255–1.238). Conclusions: The G516T polymorphism in the CYP2B6 gene is a key predictor of the therapeutic response to treatment in TB patients.